Science Literacy Ability of High School Students in the Integration of Steam Learning with Mind Mapping Techniques on Virus Materials - Rochmah, Aulia Afia; Marianti, Aditya; Martuti, Nana Kariada Tri (Universitas Negeri Semarang, 2023)
STEAM learning provides opportunities for students to apply science as a body of knowledge, a way of investigating, a way of thinking, and the interaction of science, technology and society. This study aims to improve the scientific literacy skills of class X students through the integration of STEAM learning using the mind mapping technique on viruses. This research is a pre-experimental design pre-test and post-test applied to 10th grade students of senior high school using random sampling technique. A total of 75 students from 3 different classes were accepted as participants and treated for pre-test and post-test. The instruments used to collect data were multiple choice test designs and essays based on indicators of scientific literacy ability. This study provides an explanation of the application of STEAM learning with mind mapping techniques to viral material to empower students' scientific literacy abilities. The application of STEAM learning has proven to be effective in empowering students' scientific literacy skills from low to high levels.